Extremely Low‐Frequency Electromagnetic Fields Entrain Locust Wingbeats. Issue 4 (6th April 2021) - Shepherd, Sebastian; Jackson, Christopher W.; Sharkh, Suleiman M.; Aonuma, Hitoshi; Oliveira, Eugenio E.; Newland, Philip L.
Abstract : Extremely low‐frequency electromagnetic fields (ELF EMFs) have been shown to impact the behavior and physiology of insects. Recent studies have highlighted the need for more research to determine more specifically how they affect flying insects. Here, we ask how locust flight is affected by acute exposure to 50 Hz EMFs. We analyzed the flights of individual locusts tethered between a pair of copper wire coils generating EMFs of various frequency using high‐speed video recording. The mean wingbeat frequency of tethered locusts was 18.92 ± 0.27 Hz. We found that acute exposure to 50 Hz EMFs significantly increased absolute change in wingbeat frequency in a field strength‐dependent manner, with greater field strengths causing greater changes in wingbeat frequency. The effect of EMFs on wingbeat frequency depended on the initial wingbeat frequency of a locust, with locusts flying at a frequency lower than 20 Hz increasing their wingbeat frequency, while locusts flying with a wingbeat frequency higher than 20 Hz decreasing their wingbeat frequency. During the application of 50 Hz EMF, the wingbeat frequency was entrained to a 2:5 ratio (two wingbeat cycles to five EMF cycles) of the applied EMF. We then applied a range of ELF EMFs that were close to normal wingbeat frequency and found that locusts entrained to the exact frequency of the applied EMF. These results show that exposure to ELF EMFs lead to small but significant changes in wingbeat frequency in locusts. We discuss the biological implications of the coordination of insect flight in response to electromagnetic stimuli. © 2021 Bioelectromagnetics Society.